Combination of low‐dose total skin electron beam therapy and subsequent localized skin electron beam therapy as a therapeutic option for advanced‐stage mycosis fungoides. (1st June 2018) - Kinoshita‐Ise, M.; Ouchi, T.; Izumi, E.; Kawaguchi, O.; Nagao, K.; Amagai, M.; Funakoshi, T.
Summary: Electron beam therapy (EBT) is an established treatment for mycosis fungoides (MF), but evidence for the use of EBT in advanced cutaneous conditions is limited, and optimal scheduling of the regimen for such conditions remains unclear. We report the case of a 44‐year‐old woman diagnosed with MF with widespread cutaneous lesions, including multiple huge tumours in the craniofacial area. Low‐dose total skin (TS)EBT and subsequent localized skin (LS)EBT achieved striking improvements in eruptions. Oral etretinate was also administered during therapy. Our experience implies that combined TSEBT and LSEBT may be worth attempting when a patient presents with both widespread lesions and prominent tumours, even when the tumours are extremely large.